Reflexivity, embodiment, and ethics of care in rangeland political ecology: reflections of three feminist researchers on the experience of transdisciplinary knowledge co-production - Ravera, Federica; Fernández-Giménez, Maria E.; Oteros-Rozas, Elisa (Frontiers in Human Dynamics, 2023)
Although there is a growing interest in transdisciplinary knowledge co-production approaches applied to rangeland political ecology, the research paradigms and methodologies still dominating this field of research leave little room for equitable engagement with research participants and genuine action-oriented research. In this paper we provide a reflection on new practices grounded in feminist studies of science and care ethic literature to orient a transgressive and engaged transdisciplinary political rangeland ecology research. Feminist epistemologies call for reflection on who produces knowledge and how such knowledge is used and shared. Feminist practices such as reflexivity, embodiment, reciprocity and care, cultivate awareness of the power dynamics embedded in the research process and motivate researchers to counteract asymmetrical or extractive relationships when we identify them. We first introduce the scholarship that inspires key principles of our feminist research approach, and then reflect on our experiences as researchers and as activists working with Spanish and Catalan networks of women pastoralists. Three research questions guide our reflective process: i) how can feminist theories of knowledge co-production contribute to rangeland political ecology; ii) how can feminist methodologies be applied in practice so that collaboration between women pastoralists, their organizations and researchers, are mutually reinforcing, care-full and action-oriented, iii) what are challenges and limitations from our experiences to foster transformation and emancipation in knowledge co-production processes?